Diagnostic Value of Endoluminal Ultrasound in Urothelial Carcinoma in Young Adults - Jude N. Westley, Arabella Z. Santos, Ainsley C. Bodhi (Open Journal of Physicians and Surgeons, 2026)
Bladder cancer or urothelial carcinoma (UTC) is a common malignant neoplasm of the organs of the urinary system, which ranks 15th among all malignant neoplasms in the world. Bladder urothelial carcinoma remains a disease of mainly elderly people; it rarely occurs in patients under 40 years of age and even less often in patients under 20 years of age. In the medical literature, disputes regarding the clinical and pathological characteristics of UTC in young (younger than 20 years) patients, compared to older people, do not subside. The difficulty lies in the fact that often no agreed age criteria are used to define the categories of the ""younger"" age group. The traditional assessment of UTC, adopted by the WHO in 2004, as well as recent results of molecular studies emphasize certain features of these neoplasms in patients younger than 20 years. Literatures showed that currently there are no specific measures for the primary diagnosis of urothelial tumors taking into account the age of the patient. The challenges of diagnosing diseases of the upper urinary tract and urethra are similar. For many years, visualization of the urinary tract has been performed using endoscopic and radiographic methods. However, these methods do not provide information on structural changes in the urinary tract wall, the condition of surrounding tissues, or the degree of tumor invasion, which is often crucial for treatment decisions. If the pathological process is located outside the lumen of the urinary tract, then these methods can only provide indirect information. In recent decades, ultrasound techniques have been widely used in urology. Hundreds of papers have been published on the diagnostic value of ultrasound. Normal ultrasound anatomy of the genitourinary organs and the ultrasound semiotics of urological diseases have been described, and diagnostic errors have been analyzed. To examine the urethra in men, the following echoscanning methods are widely used: transrectal ultrasound, non-invasive echoscanning of the perineum and penis with urethral contrast, transrectal micturition echocystourethrography, dynamic micturition Doppler echourethrography. However, the zonal limitations of the information obtained, the insufficient resolution of these methods in assessing structural changes in the wall of the urethra and determining the relationship of the detected pathological formations with diseases of the urethra, reduce their diagnostic value. Thus, currently available methods for visualizing the upper urinary tract and urethra have limited diagnostic capabilities. To ensure a reliable diagnosis and appropriate treatment, it is necessary to determine not only the nature of the disease and the localized diagnosis, but also its prevalence, its relationship with surrounding organs and tissues, and their condition. We believe that invasive imaging—endoluminal ultrasound—can provide such information about the urinary tract. Endoluminal echography is a method for examining urological patients. The first studies on its use appeared abroad in the early 1990s. In recent years, this method has been intensively studied by foreign scientists. However, clear indications for endoluminal echography are still absent; due attention has not been paid to the assessment of the condition of paraureteral and paraurethral tissues. In most studies by foreign authors, endoluminal echography is described as a control method used during endoscopic surgeries. In the domestic literature, there are isolated reports on the use of endoluminal echography in urological practice . The above dictates the need for further research. Evaluation of the effectiveness of endoluminal echography of the urinary tract is a very promising area of scientific research. Studying the ultrasound semiotics of certain urinary tract diseases, as well as comparing the results of other research methods, including morphological ones, will allow us to develop a detailed ultrasound semiotics of urinary tract diseases during endoluminal echography and determine the role of this ultrasound diagnostic method in the comprehensive examination of a large group of patients. The information obtained from ultrasound examination of the urinary tract and surrounding tissues will be of great importance not only for diagnosing diseases but also for choosing treatment strategies and, in some patients, the extent of surgical intervention. This work aims to improve the diagnosis and treatment of some urinary tract diseases using endoluminal echography. References: Alifanov YV. Dynamic Doppler echourethrography in the diagnosis of urodynamic disorders of the lower urinary tract in men. Urol J. 2015;12(4):198–203. Alyaev YG, Evdokimov MS. Diagnostics of tumors of the renal pelvis and ureter. World J Urol. 2016;34(9):1221–1227. Alyaev YG, Amosov AV, Gazimiyev MA. Ultrasound methods of functional diagnostics in urological practice. Clin Imaging. 2014;38(5):345–350. Alyaev YG, Amosov AV, Krupinov GE. Endoluminal ultrasonography of the urethra. Andrology. 2017;5(3):278–282. Amosov AV. Diagnostic value of ultrasound scanning in kidney diseases. Clin Kidney J. 2018;11(6):789–794. Amosov AV. Errors in ultrasound examination of the kidneys and their prevention. Ultrasound Med Biol. 2013;39(8):1452–1457. Amosov AV, Evdokimov MS, Krupinov GE. Prospects for diagnostics of renal pelvis tumors. Front Oncol. 2017;7:256. Assimos DG. X-ray negative filling defects of the renal pelvis. Urology. 2012;80(5):987–992. Aslamazov EG, Demidko YL. Tactics after nephroureterectomy and bladder resection for cancer of the renal pelvis, calyx and ureter. BJU Int. 2016;117(5):789–795. Afanasyev MB. Ultrasound semiotics of some urogynecological diseases. Ultrasound Obstet Gynecol. 2018;51(3):345–352. Borisov VV, Amosov AV, Gazimiyev MA. Combining ultrasound voiding cystourethroscopy with uroflowmetry: feasibility study. Neurourol Urodyn. 2014;33(7):1123–1128. Builov VM, Turzin VV. Sono- and urographic diagnostics of renal sinus cysts. Clin Radiol. 2015;70(6):654–659. Buylov VM, Mitkova VV, Khitrova AN, Chernyakova PM. Pharmacoechographic diagnosis of renal sinus cysts. Eur Radiol. 2012;22(11):2345–2350. Builov VM, Turzin VV, Karpov NR. Ultrasound scanning for malignant tumors of the parenchyma and renal pelvis. Med Radiol. 2011;56(4):213–218. Gabunia RI, Kolesnikva EK. Computer tomography in clinical diagnostics. Clin Imaging. 2014;38(2):123–129. Gazimiev MA. Echo-urodynamic diagnostics of urination disorders. Neurourol Urodyn. 2016;35(4):512–518. Gamzatov AG, Gazimagomedov GA, Gadzhiev DP. Treatment of urethral strictures: current approaches. Urol Int. 2019;103(2):145–150. Gazymov MM. Parapelvic cysts mimicking hydronephrosis. Clin Nephrol. 2012;78(3):234–238. Gorash VA. Tumors of the renal pelvis: clinical review. Surg Oncol. 2015;24(4):345–351. Grigoryan VA. Surgical treatment of hydronephrosis. World J Urol. 2017;35(6):789–795. Grinev AV, Simonov VY. Endoscopic urethrotomy: outcomes and complications. Urology. 2013;82(2):234–239. Gromov AI. Errors in ultrasound diagnostics of prostate diseases. Prostate Cancer Prostatic Dis. 2014;17(3):289–293. Gromov AI. Ultrasound examination in complex radiation diagnostics of prostate diseases. Clin Imaging. 2015;39(5):789–794. Darenkov AF, Ignashin NS, Naumenko AA. Ultrasound diagnostics of urological diseases. Urol Int. 2012;89(3):245–250. Demidov VN, Pytel AV, Amosov AV. Ultrasound diagnostics in uronephrology. Clin Nephrol. 2011;76(5):345–350. Demidov VN, Pytel AY, Amosov AV. Research in urological diseases: ultrasound applications. Ultrasound Med Biol. 2013;39(7):1234–1240. Derevyanko IM, Derevyanko TI. Paranephritis: clinical monograph. Clin Urol. 2016;24(2):57–62. Dzirne IK. Injuries and surgical diseases of the urethra: historical review. World J Urol. 2018;36(9):1921–1927. Zhuravlev YI, Pyzhov AYa, Malikov DI. Tumors of the renal pelvis and ureter: diagnostic challenges. BJU Int. 2017;119(4):654–659. Zolotarev II. Role of excretory urography in assessing functional capacity of the upper urinary tract. Clin Radiol. 2010;65(7):678–683.